A REVIEW ON HYPO HIDROTIC EFFECT OF SIDDHA FORMULATION - KUNGUMAPOO MATHIRAI - Rajalakshmi, S.P.; Srinivasan, V.; Ramamurthy, M.; Elansekaran, S.; Christian, G.J. (International Journal of Ayurveda and Pharma Research, 2016)
Hyperhidrosis is a condition present with excess sweating of palms on the hands, soles of the feet, forehead and axillae. This is socially embarrassing. There are few herbs to treat hyperhidrosis in Siddha system of medicine. The drug Kungumapoo Mathirai is being used in Siddha system of medicine for many years to treat hyperhidrosis. The ingredients used in the preparation of Kungumapoo Mathirai are Crocus sativus, Zingiberofficinale, Piper nigrum, Piper cubeba, Costus speciosus, Carum capticum, Piper longum, Syzygium aromaticu, Elettaria cardomom, Korosanai (Oxbile), Vengaram (Sodium biborate), Lingam (Red sulphide of mercury), Sambrani poo (Dry powder of Styrax benzoin). This article reviews the hypo hydration effect of the drug Kungumapoo Mathirai and its ingredients. This review will help to get much information on hypohydrosis effect of the chemical constituents of the drug. The antioxidant properties of the ingredients which is acting as hypo hydrating agent and their mechanism in controlling the nervous excitement by reducing the action potential in detail. The use of herbal drugs is becoming more popular due to the adverse effects of synthetic Anticholenergics and Antispasmodic drugs which are used to treat hyperhidrosis worldwide. Excellence of Siddha, formulated each and every medicines on the basis of Thiridhosa theory and five elemental theory, which are the basic principles of Siddha medicine. The basic theory of Siddha formulation Kungumapoo Mathirai is also explained here.